Israelite Religion and Biblical Theology - Miller, Patrick D. (Sheffield Sheffield Academic Press, 2000)
This is a formidable collection of previously published essays by this distinguished Old Testament scholar. Three significant areas of biblical studies have been a focus of the author's attention throughout his career: the Bible in its ancient Near Easter
Keywords: Theology - Old Testament; Bible. -- Old Testament -- Theology. Bible. -- Psalms -- Criticism, interpretation, etc. Bible. -- Deuteronomy -- Criticism, interpretation, etc